Identifying the topographic signature of early Martian oceans - Abdallah S. Zaki; Michael P. Lamb (Nature, 2026)
Abstract Planet-wide interpretations of shorelines suggest that Mars once hosted an early ocean covering one-third of its surface 1–9 . However, the elevations of these shorelines deviate from an equipotential surface by several kilometres, challenging that interpretation 3,7,10–12 . Here we investigate whether a planet that once hosted an ocean should be expected to leave discernible shorelines. We show that on Earth, the most prominent topographic signature of a global ocean is not a shoreline. Rather, it is a band of low slope and curvature values that comprises coastal plains and the continental shelf, with an elevation range of −410 m to −15 m. When applying a similar analysis to the Martian surface, we observe a comparably flat zone between approximately –1,800 m and –3,800 m elevation, potentially marking a partially preserved Martian coastal shelf. Although other processes, such as lava flows 13 , might explain flat regions locally, a coastal shelf best explains the circumglobal band of flat topography, in addition to river delta deposits 4,14–17 , coastal deposits 18 , thick sequences of layered rock 19,20 and aqueously altered minerals 20,21 , all observed within the putative coastal shelf zone. Our results support the presence of an ancient ocean on Mars and indicate that topographic shelves rather than shorelines may be better indicators of long-lived oceans.